Radicalism Discourse Analysis on Online Sites in Indonesia - Bonan Dolok Oktavianus Siagian; Arwin D.W. Sumari (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2015)
In this research, it was done an analysis of radicalism within the online site which was ever blocked by the government, namely www.arrahmah.com. In this study, seven articles were taken as samples. The study could also classify the radicalism in three (3) levels and categorizing the threat of sites in three categories based on the understanding of experts associated with the applicable rules and theories. The conclusion taken from this study is the www.arrahmah.com a very dangerous site, because the www.arrahmah.com site contains radicalism in all levels and If associated with the national security, then www.arrahmah.com site becomes a threat to Indonesia’s national interests which are written within the 2008 R.I defense white book, whether at absolute, vital, or primary level.